Aryl-substituents moderate the nature of hydrogen bonds, N-H⋯N versus N-H⋯O, leading to supramolecular chains in the crystal structures of N-arylamino 1,2,3-triazole esters - Cunha, A.C. (2014)
10.1039/c3ce40102b